Pengaruh Perencanaan Kerja, Risk Management, dan Good Governance Terhadap Kinerja Pegawai (Studi Pada Direktorat Jenderal Bina Keuangan Daerah, Kementerian Dalam Negeri) - Ramdhany, Denny; Maulina, Anita (Neraca : Jurnal Akuntansi Terapan, 2025)
In an effort to create a professional government bureaucracy with characteristics, integrated, high-performance, capable of serving the public, neutral, prosperous, dedicated, and upholding the basic values and code of ethics of the state apparatus, bureaucratic reform is implemented in government agencies. The existence of bureaucratic reform demands improvements in various aspects of governance. This study aims to determine the effect of work planning (X1), risk management (X2) and good governance (X3) on employee performance (Y), especially at the Directorate General of Regional Financial Development of the Ministry of Home Affairs. The type of research used in this research is quantitative research with descriptive analysis methods. The population in this study were all employees of the Directorate General of Regional Finance with a sample of 76 people. The results showed that work planning has a significant influence on employee performance, with a contribution of 26.5%, risk management also has a significant influence on employee performance, with a contribution of 36.6%, good governance shows the greatest influence on employee performance, with a contribution of 64.6%. While work planning, risk management, and good governance together have an influence of 65.8%, the remaining 34.2% is explained by other variables not included in the regression model. While work planning, risk management, and good governance together have an influence of 65.8%, the remaining 34.2% is explained by other variables not included in the regression model.